2010
DOI: 10.1016/j.marenvres.2009.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of a parasite, QPX, and the harmful-alga, Prorocentrum minimum on northern quahogs, Mercenaria mercenaria

Abstract: a b s t r a c tNorthern quahogs, Mercenaria mercenaria (L.), frequently are infected with the parasite Quahog Parasite Unknown (QPX, Labyrintohomorpha, Thraustochytriales), which can cause morbidity and mortality of the quahogs. Possible interactions between this parasitic disease and exposure to the harmful dinoflagellate Prorocentrum minimum in M. mercenaria were studied experimentally. Quahogs from Massachusetts with variable intensity of QPX infection were exposed, under controlled laboratory conditions, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 45 publications
2
21
0
Order By: Relevance
“…Quahog haemocytes exposed in vitro to P. minimum form aggregates surrounding algal cells, confirming previous observations of , probably to isolate P. minimum cells from the host tissues. Similarly, in vivo exposures of quahogs, Manila clams, mussels and bay scallops exposed to P. minimum showed depression of phagocytosis, induced aggregation of haemocytes surrounding the harmful algae and a large inflammatory response characterised by a massive infiltration of haemocytes into the intestine (Wikfors and Smolowitz 1993;Hégaret and Wikfors 2005a;Galimany et al 2008a;Hégaret et al 2009Hégaret et al , 2010. Present in vitro results support the hypothesis that this massive migration of haemocytes through the intestinal epithelium occurred to surround and isolate (via encapsulation) the cells of P. minimum.…”
Section: Effect Of Harmful Algal Cells On Bivalve Haemocytes and Theisupporting
confidence: 75%
See 2 more Smart Citations
“…Quahog haemocytes exposed in vitro to P. minimum form aggregates surrounding algal cells, confirming previous observations of , probably to isolate P. minimum cells from the host tissues. Similarly, in vivo exposures of quahogs, Manila clams, mussels and bay scallops exposed to P. minimum showed depression of phagocytosis, induced aggregation of haemocytes surrounding the harmful algae and a large inflammatory response characterised by a massive infiltration of haemocytes into the intestine (Wikfors and Smolowitz 1993;Hégaret and Wikfors 2005a;Galimany et al 2008a;Hégaret et al 2009Hégaret et al , 2010. Present in vitro results support the hypothesis that this massive migration of haemocytes through the intestinal epithelium occurred to surround and isolate (via encapsulation) the cells of P. minimum.…”
Section: Effect Of Harmful Algal Cells On Bivalve Haemocytes and Theisupporting
confidence: 75%
“…Our results indicated that in vitro interactions between haemocytes and P. minimum are good proxies for in vivo experiments and show consistently different haemocyte responses, according to the bivalve tested, showing no measurable effects on fundamental haemocyte functions in oysters, a decrease in phagocytosis associated to the formation of large haemocyte aggregates surrounding the algal cells in quahogs, Manila clams and blue mussels (Galimany et al 2008a;Hégaret et al 2009Hégaret et al , 2010. In addition, previous studies (Hégaret and Wikfors 2005a, b) also demonstrated that laboratory, in vivo experiments exposing bivalves to cultures of P. minimum were good proxies for field HAB exposures.…”
Section: Effects Of Bivalve Haemolymph On Algaementioning
confidence: 69%
See 1 more Smart Citation
“…This suggests that a bloom of PSP producers can weaken bivalves enough that they are much more susceptible to any additional stress. Previous studies demonstrated that HAB exposure often depressed phagocytosis and enhanced aggregation and circulating hemocyte concentration (Hé garet and Wikfors, 2005a,b;Hé garet et al, 2007bHé garet et al, , 2009Hé garet et al, , 2010. Hemocytes represent the first line of defense (Janeway, 1994) against parasites, pathogens and foreign organisms which can be either engulfed by phagocytosis or encapsulated.…”
Section: Histopathological Effects Of a Catenellamentioning
confidence: 99%
“…Harmful algae have been shown to temper as well as aggravate the host-pathogen interactions in both adult and juvenile bivalves [18,33,38]. The implications of an elevated larval PO activity are, however, largely unknown as the immunological role of PO is still poorly understood.…”
Section: Discussionmentioning
confidence: 99%